Pengaruh Penambahan Sari Kunyit terhadap Sifat Fisik dan Kimia Minuman Sari Buah Nanas - Friska Syaiful; Merynda Indriyani Syafutri; Bandhia Ayu Lestari; Sugito Sugito (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Syaiful F, Syafutri MI, Lestari AB, Sugito S. 2020. Effect of turmeric juice addition on physical and chemical properties of pineapple juice beverage. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Pineapple (Ananas comosus L.) is one of the Indonesian local fruits. Processing of pineapple into fruit juice is an effort to extend the shelf life and to increase the utility value of pineapples. Pineapple juice can be added with extracts from spices, such as turmeric, to enrich the content of functional compounds. The purpose of this research was to learn the physical and chemical properties of pineapple juice beverage with turmeric juice addition. The research used a non factorial Completely Randomized Design, with six formulations of pienapple juice and turmeric juice as treatments. The observed parameters were physical (viscosity and color include L*, a*, b*), and chemical properties (total soluble solid, total acid, vitamin C and total phenol). The results showed that the addition of turmeric juice significantly affected the increasing of a*, b* and total phenol values. Based on vitamin C and total phenol values, the formulation of 70 % pineapple juice : 30 % turmeric juice was the best treatment.